Feedstock powder processing research needs for additive manufacturing development. Issue 1 (February 2018) - Anderson, Iver E.; White, Emma M.H.; Dehoff, Ryan
Highlights: By completing these tasks researchers can promote rapid growth of AM. Both rotating disk and close-coupled gas atomization can be improved to suit AM feedstocks. The wide CC-GA industry base pushes it to the top for potential to accelerate AM. Abstract: Additive manufacturing (AM) promises to redesign traditional manufacturing by enabling the ultimate in agility for rapid component design changes in commercial products and for fabricating complex integrated parts. By significantly increasing quality and yield of metallic alloy powders, the pace for design, development, and deployment of the most promising AM approaches can be greatly accelerated, resulting in rapid commercialization of these advanced manufacturing methods. By successful completion of a critical suite of processing research tasks that are intended to greatly enhance gas atomized powder quality and the precision and efficiency of powder production, researchers can help promote continued rapid growth of AM. Other powder-based or spray-based advanced manufacturing methods could also benefit from these research outcomes, promoting the next wave of sustainable manufacturing technologies for conventional and advanced materials.